ETHICAL BEHAVIOR OF ROMANIAN STUDENTS. DOES GENDER MATTER? - LUPU, Manuela (Studia Universitatis Babeș-Bolyai Negotia, 2017)
The present research is focused on a quantitative analysis regarding the ethical attitudes of students, future practitioners, on the students’ perception towards some ethically questionable practices, with the specific aim of identifying possible differences among groups with respect to gender. The practical importance of the applicative study is illustrated by the confirmation of the idea, present in many studies, according to which male participants have more unethically as compared to female participants and the fact that unethical attitudes acquired while at university continue after graduation, in the professional activity. JEL Classification: M19